Trafficking of Mononuclear Phagocytes in Healthy Arteries and Atherosclerosis - Tomas, Lukas; Prica, Filip; Schulz, Christian (Frontiers in Immunology, 2021)
Monocytes and macrophages play essential roles in all stages of atherosclerosis – from early precursor lesions to advanced stages of the disease. Intima-resident macrophages are among the first cells to be confronted with the influx and retention of apolipoprotein B-containing lipoproteins at the onset of hypercholesterolemia and atherosclerosis development. In this review, we outline the trafficking of monocytes and macrophages in and out of the healthy aorta, as well as the adaptation of their migratory behaviour during hypercholesterolemia. Furthermore, we discuss the functional and ontogenetic composition of the aortic pool of mononuclear phagocytes and its link to the atherosclerotic disease process. The development of mouse models of atherosclerosis regression in recent years, has enabled scientists to investigate the behaviour of monocytes and macrophages during the resolution of atherosclerosis. Herein, we describe the dynamics of these mononuclear phagocytes upon cessation of hypercholesterolemia and how they contribute to the restoration of tissue homeostasis. The aim of this review is to provide an insight into the trafficking, fate and disease-relevant dynamics of monocytes and macrophages during atherosclerosis, and to highlight remaining questions. We focus on the results of rodent studies, as analysis of cellular fates requires experimental manipulations that cannot be performed in humans but point out findings that could be replicated in human tissues. Understanding of the trafficking, fate and disease-relevant dynamics of monocytes and macrophages during atherosclerosis provides an important basis for the development of therapeutic strategies to limit lesion formation and promote plaque regression.